Regulation of aflR and Its Product, AflR, Associated with Aflatoxin Biosynthesis - Liu, Biing-Hui (American Society for Microbiology, 1998)
We studied the role of the regulatory gene aflR and its product, AflR, in the biosynthesis of aflatoxin in Aspergillus. Western blot and enzyme-linked immunosorbent assay analyses revealed that aflatoxin B(1) accumulation was directly related to AflR expression and was regulated by various environmental and nutritional conditions, including temperature, air supply, carbon source, nitrogen source, and zinc availability. Expression of an aflatoxin biosynthetic pathway structural gene, omtA, was regulated by the presence of AflR. Induction patterns for aflR mRNA and AflR were correlated with that for omtA mRNA in an aflatoxin-producing strain of Aspergillus parasiticus. Analysis of non-aflatoxin-producing strains of A. flavus, A. sojae, and A. oryzae grown in medium suitable for aflatoxin B(1) production showed that both aflR mRNA and AflR production were present; however, omtA mRNA production was not detected in any of these examined strains. AflR in the A. oryzae strain was regulated by carbon source and temperature in a manner similar to that seen with A. parasiticus.